A metamodel-based knowledge sharing system for disaster management - Othman, S. H. (Elsevier Ltd, 2016)
Timely knowledge sharing in disaster management (DM) is clearly vital, but it is remains challenging. Roles involved in DM processes often cut across many organizational boundaries and are dynamic. Knowledge involved is enormous and diverse. It includes information related to varieties of disasters, roles descriptions, plans and operations. Alas, practices may also vary across different regions and authorities. This paper makes a crucial contribution to address the knowledge sharing challenge by providing a knowledge based systems approach to facilitate structuring, storing and reusing DM knowledge. The contribution of this paper is three folds: Firstly, it presents a metamodel-based architecture suitable for various distributed knowledge sharing settings; Secondly, it presents an actual implementation of such a system, the Disaster Management Knowledge Repository (DMKR1.0). DMKR facilitates collaboration and DM knowledge sharing using a tailored DM language. This offers a flexible structure to allow the storage and retrieval not only of observed and measured data, but also interpretative and inferred information of the disaster management knowledge. Thirdly, the paper provides disaster management exemplars of how DMKR users can easily instantiate DM models to communicate and to generalize their knowledge for the benefit of sharing it within their community. This presents a compelling evidence of the soundness and the effectiveness of the overall approach to DM knowledge sharing.